The Effect of Using Communicative Language Teaching on Speaking Ability - Hanafi, Rahayu Nindya Ratih, (Universitas Muhammadiyah Jember, 2016)
This research aims at investigating the impact of Communicative Language Teaching method on the improvement of students’ speaking ability. This is experimental research with non-randomized control group pretest posttest design. Class VII/A is the experimental research group, while class VII/B is the control group. Each of them consists of 22 students. Subjective test is used to collect the data about the students’ speaking ability in which the content is based on the curriculum used in the school. The data analysis used is t-test using SPSS version 16. The result of data analysis shows that p value is 0.016. The score is lower than 0.05. Seeing the result we can say that the null hypothesis (Ho) saying that there is no effect of using Communicative Language Teaching on speaking ability is rejected. It means that there is effect of using Communicative Language Teaching on the students’ speaking ability.Keywords: Communicative Language Teaching method, speaking ability.